The Globe encyclopaedia of universal information / edited by John M. Ross. - Ross, John M. (John Merry), 1833-1883, editor. (Tufts University. Tisch Library., 2015)
Volume 3 of 6.; 1 online resource (6 volumes) : illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.